2004
DOI: 10.1093/ptj/84.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Management of Postsurgical Hyperhidrosis With Direct Current and Tap Water

Abstract: Background and Purpose. Excessive sweating, known as hyperhidrosis, involves the eccrine sweat glands of the axillae, soles, palms, and/or forehead. The use of iontophoresis to reduce or eliminate excessive sweating has been described since 1952. The purpose of this case report is to describe the use of tap water galvanism (TWG) using direct current (DC) with a patient who had postsurgical hyperhidrosis. Case Description. The patient was a 36-year-old male electrician with traumatic phalangeal amputation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Tap water and normal saline iontophoresis are said to be the effective, safe, and inexpensive treatments for idiopathic hyperhidrosis with minimal adverse side effects. Similar to some findings, we showed the efficacy of our local tap water 2 , 4 , 15 , 16 ) and normal saline 11 ) in iontophoresis treatment for idiopathic hyperhidrosis. However, in contrast to some findings 11 ) , the efficacy of normal saline iontophoresis was greater (70% more efficient) than that of tap water iontophoresis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Tap water and normal saline iontophoresis are said to be the effective, safe, and inexpensive treatments for idiopathic hyperhidrosis with minimal adverse side effects. Similar to some findings, we showed the efficacy of our local tap water 2 , 4 , 15 , 16 ) and normal saline 11 ) in iontophoresis treatment for idiopathic hyperhidrosis. However, in contrast to some findings 11 ) , the efficacy of normal saline iontophoresis was greater (70% more efficient) than that of tap water iontophoresis.…”
Section: Discussionsupporting
confidence: 90%
“…Excessive palmoplantar, axillae, facial, or cervical region sweating in idiopathic hyperhidrosis usually occurs bilaterally and causes social, psychological, emotional, and professional difficulties for the afflicted. The incidence of idiopathic hyperhidrosis is reported to be between 0.6 to 2.8% in both genders 1 , 2 , 3 ) . Idiopathic hyperhidrosis may begin in childhood and continues for the rest of the subject’s life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al, (1999) 7 concluded that tap water iontophoresis is a safe and useful treatment modality for palmar hyperhidrosis. Gillick et al, (2004) 8 described the use of tap water galvanism (TWG) using direct current (DC) with a patient who had postsurgical hyperhidrosis. The patient was a 36-year-old male electrician with traumatic phalangeal amputation and postsurgical development of hyperhidrosis.…”
Section: Introductionmentioning
confidence: 99%